Sensitivity analysis of plastic hinges used in nonlinear analysis of reinforced concrete frames - Esteves, Arsenio A. Jr.; Tingatinga, Eric Augustus J. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Nonlinear static analysis or pushover analysis is widely used in design and seismic performance evaluation because of its simplicity and capability to capture the post- elastic behavior of structures. The inelastic behavior is considered in the analysis by introducing plastic hinges in the elements of the structure. Commercial software like ET ABS and SAP2000 have predefined default hinge parameters that are readily available for the users. These default hinge parameters, however, are based on FEMA-356 and ATC-40 guidelines, hence average values and certain simplifications are applied. In some cases, the default hinge properties may not be enough to capture the behavior of a given structure therefore it is important that users of such software know the limitations of the default values and have knowledge on how to tweak these hinge parameters. This study aims to investigate the effects of changes in the hinge parameters on the pushover curve of a reinforced concrete (RC) frame. This was done by analyzing breakpoints in the pushover curve that signify cracking, yielding or failure of beams and columns. Sensitivity analysis was also done on the force- displacement parameters of the plastic hinges in beams and columns. The result of the pushover analysis of typical RC frames with default plastic hinge parameters showed, that as expected, the most critical portions of the load-deformation curve are yielding and the ultimate state of the plastic hinges, dealing with reduction in stiffness and the strength capacity of the RC frame, respectively. Analyses of several frames revealed that pushover curves of RC frames are sensitive to the plastic hinge parameters of the weaker member. Also, it was shown that formation of plastic hinges in beams cause reduction in the strength capacity of the frame while plastic hinges in the column affect the displacement capacity of the reinforced concrete frame.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete construction -- Hinges -- Testing; Structural engineering -- Mathematics